Suppression of a detrimental electromagnetic resonance which affects beam position monitor readings at the European Synchrotron Radiation Facility - L. R. Carver; N. Benoist; P. Brumund; T. Brochard; F. Ewald; H. P. Marques; B. Roche; K. Scheidt; S. White (Physical Review Accelerators and Beams)
The European Synchrotron Radiation Facility is now operating a fourth generation light source, which has a reduced horizontal emittance compared to its predecessor. Since it was first commissioned, systematic fluctuations of the beam position monitor (BPM) vertical readings have rendered some BPMs to be unusable, strongly affecting the orbit stability for the nearby bending magnet beamlines. A detailed study into the vacuum chamber close to the BPM revealed two possible sources of similar type; a break in electrical continuity via a gap on the order of several micrometers close to the BPM that creates a resonant frequency within the bandpass filter frequency of the BPMs. Electromagnetic simulations have been performed and confirm that the gap generates a resonance that could be the source of the BPM reading fluctuations. A solution to the problem has been implemented; the resonance has now been suppressed and the BPMs have been returned to general operation. Some guidelines on how to avoid this type of problem for future fourth generation light sources will then be proposed.